ANALISIS TINGKAT KEUNTUNGAN USAHA TANI TOMAT (Solanum lycopersicum L.) DI KELURAHAN SINGA GEWEH KECAMATAN SANGATTA SELATAN - Nila Kusumawati; Christian Pratama Putra; Maria Odelia Niga (Jurnal Magrobis, 2022)
This study aims to find out how much income and the level of profit received by tomato commodity farmers in Singa Geweh Village, South Sangatta District, this study was carried out in 2021 in Singa Geweh Village, South Sangatta District. Sampling for farmers using the Saturated Sampling method with a total of 18 tomato farmers as respondents. The analysis method used is farming costs, revenues, income and profit levels (R/C ratio). The results showed that the amount of tomato farming income was Rp. 25 488 047/planting season and the results of the analysis of the R/C ratio of 7.7 were greater than the value of 1, so tomato farming was profitable.